2013 IEEE International Conference on Communications (ICC) 2013
DOI: 10.1109/icc.2013.6655209
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency of optical OFDM-based networks

Abstract: AbstractÑ Orthogonal Frequency Division Multiplexing (OFDM)has been proposed as an enabling technique for elastic optical networks to support heterogeneous traffic demands. In this paper, we investigate the energy efficiency of rate and modulation adaptive optical OFDM-based networks. A mixed integer linear programming (MILP) model is developed to minimize the total power consumption of optical OFDM networks. We differentiate between two optimization schemes: power-minimized and spectrum-minimized optical OFDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Similar to our work in [43], we have considered a channel bandwidth of 50 GHz for both conventional WDM and O-OFDM networks. The maximum number of subcarriers for each O-OFDM channel is 10, each of 5 GHz where two of the channels are used as guard bands.…”
Section: B Milp Model Results Analysismentioning
confidence: 99%
“…Similar to our work in [43], we have considered a channel bandwidth of 50 GHz for both conventional WDM and O-OFDM networks. The maximum number of subcarriers for each O-OFDM channel is 10, each of 5 GHz where two of the channels are used as guard bands.…”
Section: B Milp Model Results Analysismentioning
confidence: 99%
“…Thus, the different configurations of RML+SA-based models are studied in this report. [ [13][14][15][16][17][18][19] [20] [5,6,17,[21][22][23][24][25][26][27] [ 16,28] 1L1 [8] 1PM [29] 1P1 [6] The proposed RML+SA models in this work 1LM MLM ML1 MPM MP1…”
Section: Related Workmentioning
confidence: 99%
“…In Ref. [8], the authors formulated a model based on mixed integer linear programming that minimizes the IP (Internet Protocol) consumed on a variable OFDM network. However, the model considered only the power consumption of the router ports, EDFAs (Erbium-Doped Fiber Amplifiers), and tunable OFDM transponders.…”
Section: Related Workmentioning
confidence: 99%
“…Recent studies have identified OFDM (Orthogonal Frequency-Division Multiplexing) as the enabling technology for flexi-grid system networks [6][7][8][9][10][11] . In OFDM, several orthogonal carriers (each individual carrier is referred to as a subcarrier [4] ) are modulated, and the composite signal is then carried over an individual wavelength in a fiber.…”
Section: Introductionmentioning
confidence: 99%